Thuật toán tính tổng theo miền trong xử lý phân tích trực tuyến đối với các kho dữ liệu - Ban, Đoàn Văn (Journal of Computer Science and Cybernetics, 2016)
A range query applies an aggregation operation over all selected cells an OLAP data cube where the selection is  specified by providing ranges of values for numeric dimensions. We present fast algorithm for range queries for  the  most popular aggregation operation: SUM.